1157 A Report of Two Cases of Glucocorticoid Associated Cardiac Dysfunction in Noonan Syndrome. (October 2012) - Boyle, M; Cotter, M; Franklin, O; Foran, A
Abstract : Background and Aims: To review the potential exacerbating factors of cardiac function in 2 cases of Noonan syndrome. Methods: 2 cases of PTPN11 gene mutation confirmed Noonan syndrome selected for review based on clinical course. Results: Male born at 35+3 weeks with antenatal diagnosis of bilateral pleural effusion. Transferred to The Children's University Hospital on day 10 for management of malrotation; echo revealed structurally normal heart with mild pulmonary hypertension. Day 24 monocytosis and splenomegaly noted. Day 25 echo demonstrated increasing left ventricular hypertrophy (LVH) with normal function. Day 27 diagnosed with Juvenile Myelomonocytic Leukaemia and commenced on treatment with methlyprednisolone. Day 32 repeat echo showed severe LVH with near obliteration of the left ventricle. Rate of acceleration queried to be secondary to glucocorticoids. Patient died day 32 secondary to multisystem organ failure. Male born at 37+6 weeks with antenatal diagnosis of right side pleural effusion. Day 1 profound hypotension resistant to multiple ionotrope support, chest drain inserted and commenced on ionotrope resistant hypotensive dose of hydrocortisone. Echo day 1 moderate biventricular hypertrophy and structurally normal heart. Day 15 echo demonstrated severe left ventricular hypertrophy with significant cardiac compromise. Despite maximum efforts continued to deteriorate and died on day 17. Conclusions: Noonan syndrome is an uncommon condition with an association of hypertrophic cardiomyopathy in 20% to 30% of patients. In this case series complications of Noonan syndrome treated with glucocortocoids may have exacerbated cardiac function to an irreversible degree. This should be considered in the management of these patients.